Vamana Couples Fat Signaling to the Hippo Pathway. - Misra, J.R.; Irvine, K.D. (Developmental Cell, 2016)
The protocadherins Dachsous and Fat initiate a signaling pathway that controls growth and planar cell polarity by regulating the membrane localization of the atypical myosin Dachs. How Dachs is regulated by Fat signaling has remained unclear. Here we identify the vamana gene as playing a crucial role in regulating membrane localization of Dachs and in linking Fat and Dachsous to Dachs regulation. Vamana, an SH3-domain-containing protein, physically associates with and co-localizes with Dachs and promotes its membrane localization. Vamana also associates with the Dachsous intracellular domain and with a region of the Fat intracellular domain that is essential for controlling Hippo signaling and levels of Dachs. Epistasis experiments, structure-function analysis, and physical interaction experiments argue that Fat negatively regulates Dachs in a Vamana-dependent process. Our findings establish Vamana as a crucial component of the Dachsous-Fat pathway that transmits Fat signaling by regulating Dachs.